Classification of Gayo Arabica coffee ethanol extract using FTIR-PCA. Issue 1 (February 2021) - Akbar, Z; Idroes, R; Yusuf, M; Karma, T; Ginting, B; Rahimah, S; Idroes, G M; Paristiowati, M; Tallei, T E
Abstract: The classification of the bean and powder ethanol extracts of Gayo Arabica coffee has been carried out using Fourier Transform Infrared (FTIR) and Principal Component Analysis (PCA). Coffee samples were obtained from 3 locations in Bener Meriah Regency, namely Pegasing, Celala, Jagong, and 3 locations in Aceh Tengah regency, namely Permata and Bandar and Wihpesam. Each extract was analyzed by FTIR at wavenumbers in the range of 4000 - 400 cm -1 . The obtained FTIR spectra were identified by PCA. The results showed that only the PCA plot of coffee powder extract showed a grouping pattern based on the sample location, namely Bener Meriah and Aceh Tengah. This showed that the ethanol extract of coffee powder could be used as a reference in the classification of coffee samples using FTIR-PCA.